Organizational Learning Berdampak pada Kinerja Karyawan Didukung Kesiapan Berubah Karyawan Sub Direktorat Komersial dan Hubungan Pelanggan PDAM Surya Sembada Surabaya - Athallah Refi; Hesty Prima Rini (IPM2KPE, 2023)
This study aims to measure the effect of organizational learning on employee performance through readiness to change. Quantitative research methods by taking samples with non-probability sampling and purposive sampling technique methods as many as 50 employees. Data analysis technique with Smart PLS software with hypothesis testing using PLS-based SEM. The results showed that organizational learning and change readiness had an effect on employee performance at PDAM Surya Sembada Surabaya, organizational learning had an effect on change readiness and had an effect on employee performance through change readiness. In conclusion, the higher organizational learning is done, can improve employee performance and change readiness. Thus several existing programs and training related to employee performance need to be improved to improve human resources, so as to reduce customer complaints. Employees are also encouraged to have the ability to implement the desired changes and complete work within the target time through human resource development programs and organizational learning. Keywords: Employee Performance, Organizational Learning, Readiness to Change.